Lifestyle and socio-economic inequalities in diabetes prevalence in Madadeni Township, South Africa - Mposula, Zibuyile Angel; Pacza, Tünde; Szepesi, Judith; Máthé, Endre (Acta Medicinae et Sociologica, 2023)
Rapid urbanization, social inequalities, sedentary lifestyles, and unhealthy eating habits are contributing factors to the increasing prevalence of diabetes in South Africa. Data was collected from 99 residents in Madadeni, South Africa. The analysis was conducted using Microsoft Excel and the Statistical Package for Social Sciences (SPSS) V.29. The sample had a mean age of 67.4±9.4 years, with 73.74% females and 26.26% males. Majority had Grade 10 as their highest level of education (31.31%) and were retired (51.52%). The average number of household members was 6.35±2.57. The average estimated total income was R5681.82±R2585.73 per month, with 2.13±0.92 members contributing to household income. Majority (72.72%) had T2DM, while 27.27% had T1DM. The quantitative results highlight the importance of increasing awareness and providing health education to empower the affected population with self-management knowledge.